The Development and Validation of Picture Clues Towards the Reading Readiness of Grade I Learners in Oro Elementary School - Salilin , Mary Joy D. (RIRAI Publisher, 2025)
This study developed and validated picture clues to remediate the poor reading readiness of grade 1 learners in Oro Elementary School, Agusan del Sur Division for the school year 2023-2024. The study used a descriptive evaluation research design with 42 Grade I learners as the participants of the remediation. The reading readiness level of the learners was determined by the Comprehensive Rapid Literacy Assessment (CRLA) tool in the pretest as the baseline for the learners’ reading readiness level and the same tool was used in the posttest after the implementation of the developed and validated picture clues in the learners’ regular reading instruction. The ADDIE Model was used as a guide in the design and development of picture clues and was validated based on the Learning Resource Management and Development System (LRMDS) criteria by the three (3) experts in the field. The paired t-test was used to analyze if there was a significant difference between the pretest and the posttest results after the remediation. Data revealed that before the remediation, there were only 5 learners who belonged to the “Grade Ready” level, the highest level, and 37 belonged to the “Full Refresher” level, the lowest level, hence, remediation was needed. However, after the implementation of the developed and validated picture clues as remediation, the number of learners who belonged to the “Grade Ready” level increased from 5 to 35, 2 at the “Light Refresher” level, and no one belonged to the “Moderate Refresher” and “Full Refresher” levels. Hence, exposure to the developed and validated picture clues significantly improved the learners’ reading readiness level and was a valuable tool for educators to improve reading readiness of the Grade 1 learners.